Governance.com: Democracy in the Information AgeGovernance.com: Democracy in the Information Age, edited by Kamarck Elaine Ciulla Nye Joseph S. Jr. Washington, DC: Brookings Institution Press, 2002. - Gibbons, Michael (Academy of Management Review, 2004)
From the Publisher: Advances in information technology are constantly transforming democratic governance. Power over information has become decentralized, fostering new types of community as well as different roles for government. This fascinating volume explores the many ways in which today's information revolution is changing our institutions of governance. The contributors illuminate many of the promises – and the daunting challenges – of democratic government in a rapidly changing world of networks, information, and enhanced communication. Governance.com was developed by the Visions of Governance in the 21st Century project at Harvard University's John F. Kennedy School of Government.